Penerapan Discovery Learning berbasis Eksperimen terhadap Keterampilan Proses Sains - Dwi Jayanti, Ima; Saputro, Eko Fery Haryadi; Lestari, Novika (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2026)
This research aims to improve students' science process skills through the application of an experiment-based Discovery learning model to sound materials in class VIII B SMPN 6 Nanga Pinoh. The research method used is quantitative, with a pre-experimental design of one group, pre-test and post-test design. The main instrument is in the form of pre-test and post-test questions, which include six indicators of science process skills: observing, proposing hypotheses, conducting experiments, interpreting, applying concepts, and communicating. Supporting instruments are in the form of student response questionnaires and observation sheets. The research data shows that the average pre-test score of 36,00 students increased to 69.19 in the post-test. The N-Gain value of 0.508 is in the medium category, indicating an improvement in students' science process skills after the implementation of the experiment-based Discovery learning model. The observation data showed the active involvement of students during the process and the questionnaire data also showed that the students responded positively to the learning process. The results showed that the application of experiment-based Discovery learning can improve students' science process skills.